2013
DOI: 10.1074/jbc.m113.472456
|View full text |Cite
|
Sign up to set email alerts
|

Dna2 Is Involved in CA Strand Resection and Nascent Lagging Strand Completion at Native Yeast Telomeres

Abstract: Background: DNA2 helicase/nuclease participates in telomere maintenance by unknown mechanisms. Results: dna2 mutants show slightly shortened telomeric GT-overhangs and accumulate small, nascent lagging strand DNA chains at telomeres. Conclusion: Unlike at DSBs, additional nucleases largely compensate for the simultaneous loss of Dna2 and Mre11 in producing GT. Significance: FEN1, Dna2, or Exo1 is necessary to mature lagging strands at telomeres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 110 publications
2
13
0
Order By: Relevance
“…Interestingly, the telomeres of chk1 Δ dna2 Δ, mec1 Δ dna2 Δ, rad17 Δ dna2 Δ, and ddc1 Δ dna2 Δ cells were long, and in fact longer and more diffuse, than pif1 Δ strains, known to have very long telomeres (Schulz and Zakian, 1994) (Figure 3c, Figure S4, Figure S6). In contrast, and as reported before, rad9 Δ dna2 Δ telomeres were slightly shorter than the wild type length (Budd and Campbell, 2013). Rad9 is unique amongst checkpoint proteins because it binds chromatin and inhibits nuclease activity at telomeres and DSBs (Bonetti et al, 2015, Ngo and Lydall, 2015).…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Interestingly, the telomeres of chk1 Δ dna2 Δ, mec1 Δ dna2 Δ, rad17 Δ dna2 Δ, and ddc1 Δ dna2 Δ cells were long, and in fact longer and more diffuse, than pif1 Δ strains, known to have very long telomeres (Schulz and Zakian, 1994) (Figure 3c, Figure S4, Figure S6). In contrast, and as reported before, rad9 Δ dna2 Δ telomeres were slightly shorter than the wild type length (Budd and Campbell, 2013). Rad9 is unique amongst checkpoint proteins because it binds chromatin and inhibits nuclease activity at telomeres and DSBs (Bonetti et al, 2015, Ngo and Lydall, 2015).…”
Section: Resultssupporting
confidence: 78%
“…Furthermore, in fission yeast Dna2 was shown to be involved in the generation of G-rich ssDNA at telomeres (Tomita et al, 2004). Importantly, it was reported that dna2 Δ rad9 Δ cells have abnormally low levels of telomeric 3’ G-rich ssDNA (Budd and Campbell, 2013). Consistent with what was reported for rad9 Δ dna2 Δ, chk1 Δ dna2 Δ, mec1 Δ dna2 Δ, rad17 Δ dna2 Δ, ddc1 Δ dna2 Δ and pif1 Δ dna2 Δ cells all showed low levels of 3’ G-rich ssDNA at telomeres in comparison with DNA2 strains (Figure 3a-b, Figure S3, Figure S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although the nuclease activity of Dna2 is essential for viability(Budd et al, 296 2000), the absence of Dna2 during S-phase is not obviously detrimental to exponentially 297 dividing S. cerevisiae cells. It is possible that Dna2 is required for the cleavage of only a small 298 number of Okazaki fragment 5' flaps -either long flaps generated by low levels of ongoing 299 nuclease cleavage, or those in specific, late-replicating repeat regions such as telomeres(Budd and Campbell, 2013;Markiewicz-Potoczny et al, 2018) or the rDNA repeat(Villa et al, 2016).…”
mentioning
confidence: 99%
“…Extensive resection by Apollo is inhibited by the binding of Pot1b to the ssDNA [201]. In yeast, Dna2 has also been suggested to be involved in limited processing of the 5′ strand to maintain the telomere length and telomerase binding [203,204]. While 5′ strand resection is important for telomere maintenance, over-resection could lead to telomere shortening, senescence, and other deleterious consequences [198].…”
Section: Dna Resection At Telomeres Stalled Replication Forks and Hmentioning
confidence: 99%